(untitled) (Fiep Bulletin - online, 2014)
The vaccination campaigns have shown, over time, the significance of vaccinating and to track the calendar of the SUS, as well as being aware of the benefits and efficacy of vaccines. Objective: Verify the knowledge of the research subjects about the importance of vaccination as well as evaluate the opinion about its benefits and harms. Methods: This is a descriptive, transversal and quantitative study of which 50 people agreed to participate in the research, by answering to a form containing objective questions which have been used as variables. The data, once compiled, were presented in tables and simple frequency graphs expressed in numbers and percentage. The ethical aspects were respected, according to Resolution Nº 196/96 (CNS-MS). Results: 76% of vaccinated respondents didn’t suffer any adverse reactions; 84% shown to be satisfied with the service; 72% did not wait in queues, and 86% were aware or have had access to information about vaccination campaigns, and all, without exception, proved to be in favor of vaccination. Conclusion: The obtained results suggest that in the view of the research subjects, vaccination is important to prevent diseases which may involve thousands of people and even providing some risk, there is satisfaction with the service offered by the SUS immunization, which is efficient at achieving their campaigns.